2010
DOI: 10.1111/j.1476-4431.2010.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical practice of CPCR in small animals: an internet‐based survey

Abstract: CPCR is heterogeneously performed in small animal veterinary medicine; differences exist, both among and within different types of veterinarians with varying levels of expertise, in respect to available infrastructure, personnel and CPCR techniques used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
(63 reference statements)
0
40
0
Order By: Relevance
“…As discussed, there are veterinary reviews and recommendations available on CPR initiation, delivery, and postarrest care . However, despite what may be available as a standard of care, when veterinary practitioners were surveyed, it was discovered that many of these recommendations are not being practiced . It is possible that the information is not well disseminated, formal consensus recommendations are not available, or resources (including equipment, drugs, and personnel) may be limited.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, there are veterinary reviews and recommendations available on CPR initiation, delivery, and postarrest care . However, despite what may be available as a standard of care, when veterinary practitioners were surveyed, it was discovered that many of these recommendations are not being practiced . It is possible that the information is not well disseminated, formal consensus recommendations are not available, or resources (including equipment, drugs, and personnel) may be limited.…”
Section: Prognosismentioning
confidence: 99%
“…28,42 This term can still be found in the literature; however, the AHA 2010 Guidelines and current human literature predominantly use the term CPR which includes the goal of an intact neurological patient. 10,43 As the recommendations in human medicine are reevaluated, further research in experimental animal models and clinical studies may offer benefit to our clinical small animal patients. However, the results of such studies and the recommendations gleaned from them must be critically evaluated prior to accepting them as the standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…Suggestions for CPR were extrapolated from human medicine and from expert veterinary opinion with no definitive recommendations . An Internet‐based study showed there to be considerable variation in CPR techniques used across general and referral practices . It has been suggested that this disparity in techniques was in part due to a lack of accepted, evidence‐based guidelines for CPR in cats and dogs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study 1 published in JVECC suggests considerable variation in CPR technique among veterinary practitioners, and variable compliance with accepted, peer‐reviewed guidelines. These current recommendations for veterinary CPR are composites of the opinions of individual veterinary experts and of recent American Heart Association (AHA) guidelines for CPR 2–5 .…”
mentioning
confidence: 99%
“…These current recommendations for veterinary CPR are composites of the opinions of individual veterinary experts and of recent American Heart Association (AHA) guidelines for CPR 2–5 . It is our belief that the lack of true evidence‐based veterinary CPR guidelines and standardized veterinary CPR training are major contributors to the variation noted in the study by Boller et al 1 More importantly, this variability in approach may also compromise patient outcomes. In human medicine, the advent of a widely used, cohesive educational strategy in CPR, a powerful tool to improve outcomes after cardiac arrest, was only possible when consensus was reached on optimal CPR technique.…”
mentioning
confidence: 99%